2015
DOI: 10.1161/hypertensionaha.114.04798
|View full text |Cite
|
Sign up to set email alerts
|

Denervation of the Renal Arteries in Metabolic Syndrome

Abstract: Chronic elevation of sympathetic nervous system is a key factor in metabolic syndrome. Because renal denervation (RDN) is thought to modulate sympathetic activity, we performed the Denervation of the Renal Arteries in Metabolic Syndrome (DREAMS)–study to investigate the effects of RDN on insulin sensitivity and blood pressure (BP) in patients with metabolic syndrome. Twenty-nine patients fulfilling the criteria for metabolic syndrome and who used a maximum of 1 antihypertensive or 1 antidiabetic drug or 1 of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 38 publications
(34 reference statements)
0
37
1
6
Order By: Relevance
“…It was shown that the procedure was associated with improvement in glucose metabolism (100), diastolic function (17), health-related quality of life (89) and arterial stiffness (64), and a reduction in left ventricular mass (17) in those with resistant hypertension. On the other hand, a recent study (173) showed no improvement in insulin sensitivity after one year following renal denervation in hypertensive patients with the metabolic syndrome despite a reduction in blood pressure. Chronic baroreflex activation.…”
Section: Interventions To Treat Hypertension and Their Potential Benementioning
confidence: 87%
See 1 more Smart Citation
“…It was shown that the procedure was associated with improvement in glucose metabolism (100), diastolic function (17), health-related quality of life (89) and arterial stiffness (64), and a reduction in left ventricular mass (17) in those with resistant hypertension. On the other hand, a recent study (173) showed no improvement in insulin sensitivity after one year following renal denervation in hypertensive patients with the metabolic syndrome despite a reduction in blood pressure. Chronic baroreflex activation.…”
Section: Interventions To Treat Hypertension and Their Potential Benementioning
confidence: 87%
“…The consequences of renal ablation may be due to blockade of both afferent and efferent neural pathways. One study (65) showed that ablation of afferent renal nerve activity leads to decreased MSNA, indicating a suppression of overall sympathetic vasoconstrictor drive that contributes to the antihypertensive actions; however, two recent reports (19,173) are inconsistent with this possibility. Likewise, in dogs with obesity-related hypertension, renal denervation did not decrease global sympathetic nervous activity (98).…”
Section: Interventions To Treat Hypertension and Their Potential Benementioning
confidence: 99%
“…Although producing a modest fall in arterial pressure in 29 obese patients with metabolic syndrome treated with a maximum of one antihypertensive drug, renal nerve ablation failed to decrease MSNA at a 6 mo follow-up (84). In an ovine model of heart failure, catheter-based renal denervation did not reduce elevated levels of cardiac sympathetic nerve activity when measured 24 h after renal denervation (7).…”
Section: Other Potential Determinants Of the Antihypertensive Responsmentioning
confidence: 91%
“…83 This disruption of the SNS has the potential to influence many other clinical entities highly dependent on SNS hyperactivity, such as the sleep apnea syndrome, chronic heart failure, atrial fibrillation (AF) and ventricular arrhythmias, metabolic syndrome, chronic kidney disease, and polycystic ovary syndrome. [84][85][86][87][88][89] Most of these studies are small and purely observational. Regarding cardiac arrhythmias, SYMPLICITY AF is a prospective, randomized, multicenter, feasibility clinical study investigating pulmonary vein isolation and renal denervation compared to pulmonary vein isolation alone, for the treatment of paroxysmal or persistent AF in patients with both AF and HT.…”
Section: No 4-is Rdn Safe?mentioning
confidence: 99%